P8 Sudden cardiac death in childhood. (2nd March 2016) - Donne, G Delle; Prasad, S; Kimberley, P; Sheppard, M; Daubeney, P
Abstract : Introduction and objectives: Sudden cardiac death (SCD) in the paediatric population is an uncommon event. No clear information is available regarding the prevalence of the various causes in the entire population and studies usually reflect the accumulation of autopsy cases in a single centre. We performed a retrospective study from the SCD database in our Institution based on national referrals for SCD in order to characterise the potential underlying cause of SCD in the paediatric population. Methods: We evaluated all patients under the age of 18 with who were referred to our Institution for post mortem examination from 1991 to 2013. Results: We identified 398 patients (266 female). The median age at death was 14 (minimum 0, maximum 17). 39% of death occurred whilst the child was at rest; 22% on or immediately after exercise (Figure 1 ). In 21 patients (5%) there was known congenital heart disease. In 31% of patients there was a family history of SCD, in 14% of CM, and in 5% of arrhythmia. In 18% of patients syncope had been previously reported prior to death but many had no symptoms (Figure 2 ). The main cause of death was sudden arrhythmic death (SAD) 54% followed by cardiomyopathy (CM) 15%, miscellaneous 11%, congenital heart disease 8%, myocarditis 6% and coronary anomalies 5% (Figure 3 ). Conclusions: Sudden death in the paediatric population is caused by presumed primary arrhythmia syndrome in just over half of all cases. In our series we found CM as the second leading cause of death. Knowledge of these causes and their relative prevalences is of great clinical utility, and particularly awareness of their exact morphology can help plan preventative strategies to reduce their future occurrence.